SÍNDROME DE SUPERPOSIÇÃO E ASSOCIAÇÃO DE PANICULITE E AMILOIDOSE - RELATO DE CASO - Tatiana de Souza Pina Lobo; Luciana Rodrigues de Alencar; Thiago de Carvalho Barros; Adriana Guimarães de Farias; Nilzio Antônio da Silva; Jozelia Rêgo (UniEVANGÉLICA, 2017)
Objective: To describe a clinical case of a 46-year-old woman, with overlap of systemic sclerosis and rheumatoid arthritis who develop panniculitis septal and amyloidosis. Case report: A 46-year-old female patient with a diagnosis of overlap syndrome (systemic sclerosis and rheumatoid arthritis) eight years ago evolves with pain and enlargement of the legs . After the hypothesis of panniculitis, the patient was medicated with antiinflammatory drugs and did not obtain improvement. Subjected to skin biopsy of the right leg, histopathological findings were compatible with amyloidosis and discrete panniculitis septal. Final considerations: The presence of panniculitis, which is difficult to respond to antiinflammatory treatment, should lead to the investigation of infiltrative diseases, such as amyloidosis. The presence of amyloid deposits in the dermis implies the investigation of systemic disease